Maxillary Sinus Floor Enlargement: Literature Review - Bangarashetti, Sadhana P.; Kunchur, Pavan (Journal of Contemporary Medical Practice, 2024)
Aim: The aim is to study the development of the maxillary sinus floor augmentation (MSFA) procedure. Materials and methods: Articles related to the subject were searched in Google Scholar, PubMed, Scopus and ScienceDirect databases, using keywords in various combinations. Results: Articles, included in this review described clinical, experimental studies and few reviews of the literature. The articles considered anatomy of the maxillary sinus, MSFA techniques, preoperative diagnosis and complications in MSFA, tissue repair materials used in a maxillary sinus floor augmentation procedure. Conclusion: In the past, MSFA was used only with the aim to repair defects resulting from traumatic injuries or resective oncological surgeries, today it is a predictable technique for bone augmentation in cases of subantral bone deficiency. In modern implantological practice, the procedure is aimed to obtain the quality and volume of the newly formed bone, suitable for placement of osteointegratable implants. With the development of technology, CBCT has established itself as the gold standard in preoperative preparation, and the trend towards performing MSFA is aimed at reducing the invasiveness of the procedure through various techniques, one of which is the endoscopically guided MSFA.